BEST PRACTICE PENDIDIKAN AGAMA ISLAM DI SMAN 2 SERANG BANTEN - S. Sumarni (Badan Litbang dan Diklat Kementerian Agama RI, 2016)
This research is aimed at determining how Islamic Religious Education (PAI) with preeminence at SMAN 2 of Serang, Banten. This Islamic Religious Education best practice uses descriptive – qualitative method. This research shows that SMAN 2 of Serang, Banten has preminent Islamic Religious Education practice. It means that PAI learning process at SMAN 2 of Serang has successfully changed the students’ religious attitude and behavior. This preeminence can be seen from innovations developed in PAI learning such as PAI curriculum innovation, PAI learning practice innovation, and IT use in learning PAI. There are many factors supporting PAI learning at SMAN 2 of serang such as extra-curriculum activities (Islamic Spirituality Organization / Kerohanian Islam), zikir Akbar, religious activities and religigious culture, etc. Islamic Religious Education preeminence at this school is also supported by various factors such as the headmaster’s policy, school management, cooperation with any other institutions, school environment, and also various facilities and infrastructures of PAI learning. However, there are various factors hampering the success of PAI such as incompleteness of facilities and infrastructures of PAI Lab, number of PAI teachers with respect to ratio of teachers to students, and the lack of training for teachers. Penelitian ini bertujuan untuk mengetahui bagaimana penyelenggaraan Pendidikan Agama Islam (PAI) berkeunggulan di SMAN 2 Serang Banten. Penelitian best practice Pendidikan Agama Islam ini menggunakan metode deskriptif kualitatif. Hasil penelitian menunjukkan bahwa SMAN 2 SERANG Banten memiliki praktek Pendidikan Agama Islam yang unggul. Artinya praktek pembelajaran PAI di SMAN 2 Serang berhasil mengubah sikap dan perilaku keagamaan siswa. Keunggulan ini bisa dilihat dari berbagai inovasi yang dikembangkan dalam pembelajaran PAI seperti inovasi kurikulum PAI, inovasi praktek pembelajaran PAI, dan penggunaan IT dalam pembelajaran PAI. Banyak faktor yang mendukung keberhasilan pembelajaran PAI di SMAN 2 Serang seperti kegiatan ekstrakurikuler (Kerohanian Islam), zikir Akbar, kegiatan keagamaan dan religigious culture, dan sebagainya. Keunggulan Pendidikan Agama Islam di sekolah ini juga didukung oleh berbagai faktor seperti kebijakan kepala sekolah, managemen sekolah, kerjasama dengan lembaga lain, lingkungan sekolah, dan juga berbagai sarana prasarana pembelajaran PAI. Namun demikian masih ada beberapa faktor yang menghambat keberhasilan PAI seperti masalah kelengkapan sarana prasarana terutama kelengkapan laboratorium PAI, jumlah guru PAI terkait dengan rasio guru – siswa, dan kurangnya pelatihan guru.